Grass-shrub coexistence: understanding root distribution in ecological sites of the Semiarid Chaco, Argentina - Ledesma, Roxana Ramona (2021)
The objective of this study was to analyze the root distribution of grasses and shrubs, at different soil depths, in two ecological sites (ES): highland (forest) and lowland (grassland). The root density (RD) estimation was used as a proxy to test the two-layer hypothesis. Three trenches were dug in both ES and the number of roots m−2 was registered at different depth classes. The roots were classified in categories: (a) life forms (LF), grasses and shrubs and (b) root size (diameter): fine (<0.1 cm), small (0.11–0.5 cm); medium (0.51–1.5 cm) and large (>1.51 cm). Soil bulk density (Bd) was assessed by gravimetric method and its relation with RD was determined by regression analysis. RD was analyzed by using ANOVA with the factors: ES, LF, depth and root size. There were no significant differences in RD between the ES but RD significantly decreased with depth in both ES. In the upper horizons of the forest, there was higher shrubs RD (764 roots m2) than grass RD (128 roots m2) (p < 0.0001). In grassland, grass RD was registered in all the depths. Mean fine root density was greater than the mean of other root size categories. The relationship between RD and Bd was negative and only significant in the forest (p = 0.009). The distribution of roots of both LF in the soil profile of both ES did not respond completely to the two-layer hypothesis since in upper horizons an overlap was observed.